(untitled) (Fiep Bulletin - online, 2011)
The Dance Project is part of the Open School / School Experience, and educational referrals in their being related to issues of teaching and learning, encompassing various teaching methodologies and different styles of dance. Thus the aim of this study was to identify possible contributions to the Project Dance Program Open School / School Live to changes in social behavior such as respect, kindness and commitment of participants in the activities offered at the Dance Project. The research is characterized as descriptive exploratory. The participants were 16 individuals of different ages, genders and socio-cultural effects that are embedded, integrated and participating effectively in a dance class of the Project, as well as the professional responsible for dance lessons of the project and the general coordinator of the program. The instruments used were interviews and questionnaires, subsidies that have brought us to visualize that there are changes in social behavior related to respect, commitment, warmth, self-esteem and that when they dance they are happiest, most beautiful and important and they are using dance as a way of expressing themselves. We understand that the Bill Dance has become a way of developing not only motor behavior, but the socio-affective which is the objective of the Project and the Open School Program / Living School.